2022
DOI: 10.1364/oe.450423
|View full text |Cite
|
Sign up to set email alerts
|

Realizing PIT-like transparency via the coupling of plasmonic dipole and ENZ modes

Abstract: Plasmon induced transparency (PIT), known as the coupling of plasmon modes in metamaterials, has attracted intensive research interests in photonic applications. In this work, a PIT-like transparency is realized via the strong coupling of plasmonic dipole and epsilon-near-zero (ENZ) mode. Two types of metasurfaces, namely the gold nanoantenna and dolmen-like metasurface, are designed with an integrated ENZ material aluminum doped zinc oxide (AZO) film. Simulations with the finite element method (FEM) demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Previous research has shown that the planar ENZ film exhibits typical angular dependence. 37 Oblique incidence and insensitive polarization are frequently necessary in the application of MIR radiation materials. As shown in figures 4(c) and (d), for TM polarization, as the incident angle reaching 20°, the resonant peak of another ENZ mode is excited due to the effective permittivity crossing zero at the wavelength of 10.8 mm (figure 4(b)).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that the planar ENZ film exhibits typical angular dependence. 37 Oblique incidence and insensitive polarization are frequently necessary in the application of MIR radiation materials. As shown in figures 4(c) and (d), for TM polarization, as the incident angle reaching 20°, the resonant peak of another ENZ mode is excited due to the effective permittivity crossing zero at the wavelength of 10.8 mm (figure 4(b)).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the aforementioned ENZ materials for near infrared applications, several ENZ materials have been discovered for emission applications over mid-infrared [33,34] and far-infrared wavelength [35,36]. Aluminum doped zinc oxide (AZO) has plasmonic response in the near and mid-infrared region [33,37] and tunability by adjusting the density of free electrons [34,38,39]. Rensberg et al [39] demonstrated that the wavelength at which the permittivity of AZO is equal to zero can be arbitrarily controlled from 3.7 to 9.2 mm by varying the freecarrier concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…By exciting the anapole, tailored dielectric nanomaterials can provide similar opportunities to their metallic counterparts. Such a novel dielectric photonic state provides potential applications in local near-field enhancement, , nonlinear optical effect, photocatalysis, and refractive index sensors. , …”
Section: Introductionmentioning
confidence: 99%